Review : Youngters solving mathematical problems with technology. The results and implications of the problem@web project - Villarreal, Mónica Ester (2025)
Fil: Villarreal, Mónica Ester. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía, Física y Computación; Argentina.